The Growth of Chinese Tourism in Rovaniemi : Case Study: Santa Claus Village - Luo, Liuwei (Lapin ammattikorkeakoulu, 2017)
The main purpose of this thesis is to study Santa Claus Village and improve the marketing for attracting more tourists. Therefore, the method of the thesis is case study. The strategy of the case study is survey. Hence, the survey is about how tourists think of Santa Claus Village, the postcards, the souvenirs and so on. The other aim of this thesis is to discuss the relationship between Chinese tourists and the tourism industry of Finland. In the thesis, tourism from the Global point of view is discussed including Finland and China. In the conclusion of the tourism chapter, the growth of Chinese tourism in Finland is shown by official data. In the last chapter, the innovation ideas have been put forward, Chinese pre-wedding photography is a priority among priorities of those ideas. There is not enough information of the innovation idea of Chinese pre-wedding photography. Hence, it is hard to analyse the potential market exactly without real data support.